2014
DOI: 10.1111/jpim.12242
|View full text |Cite
|
Sign up to set email alerts
|

Trust Formation in University–Industry Collaborations in the U.S. Biotechnology Industry: IP Policies, Shared Governance, and Champions*,†

Abstract: Haggling over rights to potential inventions can be a major roadblock to successful university-industry (UI) collaborations. Yet such collaborations are critical for innovation in science-based industries. This study examines the roles of universities' intellectual property (IP) policies and of shared governance for trust formation between academe and industry. The study also examines how UI champions moderate this process and how trust between university and industry partners affects UI collaboration outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 48 publications
3
111
1
4
Order By: Relevance
“…Then comes the identification and reinforcement of the strong and weak points of the universities, the role of government in management, the stabilization of relations and finally, the business results from an economic perspective and the contribution made to the university institution (Salled & Omar, 2013; -704-Intangible Capital -https://doi.org/10.3926/ic.990 Kalar & Antoncic, 2015;Casimiro & Macamo, 2016;Chen et al, 2016;Fu & Li, 2016;Giunta et al 2016). Bastieler et al (2015) propose that transparency in the management of intellectual property analysis at universities ensures greater confidence in UBRs by their members.…”
Section: Discussion Of the Topic: The Economic Impact Of The Universimentioning
confidence: 99%
“…Then comes the identification and reinforcement of the strong and weak points of the universities, the role of government in management, the stabilization of relations and finally, the business results from an economic perspective and the contribution made to the university institution (Salled & Omar, 2013; -704-Intangible Capital -https://doi.org/10.3926/ic.990 Kalar & Antoncic, 2015;Casimiro & Macamo, 2016;Chen et al, 2016;Fu & Li, 2016;Giunta et al 2016). Bastieler et al (2015) propose that transparency in the management of intellectual property analysis at universities ensures greater confidence in UBRs by their members.…”
Section: Discussion Of the Topic: The Economic Impact Of The Universimentioning
confidence: 99%
“…For example, dedicated biotechnology firms (DBFs) operate on the cutting edge of research by pushing the frontiers of science while exploring opportunities for commercialisation (Momma and Sharp, 1999). To do so, they often rely on identifying universities' research in the early stages when new or breakthrough discoveries typically emerge (Bstieler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that in addition to lowering the uncertainty of interactions in the context of technological innovations at large, for instance by regulating the intellectual property rights [62], rules and laws can also act as underlying mechanisms to align the economic and environmental objectives in the quest for eco-…”
Section: Social Sustainability Practicesmentioning
confidence: 99%